The Younger the Happier - Agustina, Sherly (Universitas Pendidikan Indonesia, 2018)
ABSTRACT: The school should be a place to spend time by playing and enjoying their childhood and adolescene. So, the school should not to becomes the main source of stress for the child. This research aimed to identify the difference in the happiness of students based on gender, age, and classâ€™ level, as well as identify the aspects that affect the happiness of students. This research uses a quantitative approach. The sample numbered 332 respondents was selected using simple random sampling techniques, with details of the student's 112 students grade 10; 108 students grade 11; and 112 students grade 12. The instruments used in the form of a detailed questionnaire â€œHappiness in Schoolâ€ compiled by researcher with reference to the five aspects of happiness according to M.E.P. Seligman (2011), which are: Positive emotion, Engagement, Relationships positive, Meaning of life or Meaningfulness, and Accomplishment categories, abbreviated as PERMA. Analytical technique used in this research is t-test, ANOVA (Analysis of Variance), and multiple regressions. There are two findings of this research, namely: the existence of a distinction based on age of happiness as well as aspects of the engagement is the most influential aspect of studentâ€™s in school. Based from these findings, it is expected that the teacher could design a class regarding to the aspects of engagement, which can increase happiness. KEY WORD: Happiness; Source of Happiness; School; Adolescent; PERMA.Â ABSTRAKSI: â€œYang Muda yang Bahagiaâ€. Sekolah harus menjadi tempat untuk menghabiskan waktu dengan bermain dan menikmati masa kecil dan remaja mereka. Jadi, sekolah seharusnya tidak menjadi sumber utama stres bagi anak. Penelitian ini bertujuan untuk mengidentifikasi perbedaan kebahagiaan siswa berdasarkan jenis kelamin, usia, dan jenjang kelas, serta mengidentifikasi aspek yang mempengaruhi kebahagiaan siswa. Penelitian ini menggunakan pendekatan kuantitatif. Sampel berjumlah 332 responden dipilih dengan menggunakan teknik random sampling sederhana, dengan rincian 112 siswa kelas 10; 108 siswa kelas 11; dan 112 siswa kelas 12. Instrumen yang digunakan berupa kuisioner â€œBahagia in Sekolahâ€ disusun oleh peneliti dengan mengacu pada lima aspek kebahagiaan menurut M.E.P. Seligman (2011), yaitu: â€œPositive emotionâ€ (Emosi positif), â€œEnggagementâ€ (Keterlibatan), â€œRelationship positiveâ€ (Hubungan positif), â€œMeaning of life or Meaningfulnessâ€ (Hidup bermakna), dan â€œAccomplishmentâ€ (Berprestasi), disingkat PERMA. Teknik analisis yang digunakan dalam penelitian ini adalah uji t, ANOVA (Analisis Varians), dan regresi jamak. Terdapat dua temuan dari penelitian ini, yaitu: adanya perbedaan kebahagiaan berdasarkan usia serta aspek keterlibatan yang merupakan aspek paling berpengaruh terhadap kebahagiaan siswa selama berada di sekolah. Berpijak dari temuan tersebut, diharapkan guru dapat merancang pembelajaran dengan memperhatikan aspek keterlibatan para siswa yang dapat meningkatkan kebahagiaan mereka. KATA KUNCI: Kebahagiaan; Sumber Kebahagiaan; Sekolah; Remaja; PERMA.About the Author: Sherly Agustina, S.T.P. is a Postgraduate Student at the Study Program of Education Psychology SPs UPI (School of Postgraduate Studies, Indonesia University of Education), Jalan Dr. Setiabudi No.229 Bandung 40154, West Java, Indonesia. For academic interests, the author is able to be contacted via her e-mail address at: sherlyagustinaa@gmail.comÂ Suggested Citation: Agustina, Sherly. (2018). â€œThe Younger the Happierâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 3(1), March, pp.45-58. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (December 25, 2017); Revised (February 14, 2018); and Published (March 30, 2018).